产神经酸菌种的筛选及发酵条件优化Screening of nervonic acid-producing bacteria and optimization of fermentation conditions - 宋贤娟1，孙爱娣1，张瑞2，周佩蓉1，黄艾祥1，王雪峰1,2 SONG Xianjuan1, SUN Aidi1, ZHANG Rui2, ZHOU Peirong1, HUANG Aixiang1, WANG Xuefeng1,2 (Zhongguo youzhi)
旨在为神经酸的获取及相关研究提供参考，以云南特色木本植物油辣木籽油为底物，从4种产油菌株中筛选出产神经酸较高的菌种，通过单因素实验和响应面实验对优选菌种的发酵条件进行了优化，并采用气相色谱-质谱（GC-MS）测定了添加与不添加辣木籽油乳液（辣木籽油、水、吐温80体积比2∶ 2∶ 1）发酵获得的优选菌种冻干粉中脂肪酸组成及含量。结果表明：圆红冬孢酵母（GDMCC 2226）为产神经酸最优菌种；圆红冬孢酵母（GDMCC 2.226）最佳发酵条件为辣木籽油添加量7%(以乳液形式添加)、菌液添加量10%、培养温度28 ℃、培养时间48 h，在此条件下圆红冬孢酵母（GDMCC 2.226）提取物中神经酸含量为2.40 mg/mL；未添加辣木籽油乳液发酵获得的圆红冬孢酵母（GDMCC 2.226）冻干粉（对照组）中饱和脂肪酸、单不饱和脂肪酸和多不饱和脂肪酸相对含量分别为38.91%、41.92%、19.18%，神经酸含量为10.983 μg/g，而添加辣木籽油乳液发酵获得的圆红冬孢酵母（GDMCC 2226）冻干粉中饱和脂肪酸、单不饱和脂肪酸和多不饱和脂肪酸相对含量分别为48.57%、3198%、19.46%，神经酸含量为13.518 μg/g，比对照组中神经酸含量提升了23.1%。综上，添加辣木籽油底物可以提高菌种冻干粉中神经酸的绝对含量。In order to provide reference for the acquisition and related studies of nervonic acid, Yunnan′s characteristic woody oil Moringa oleifolia seed oil was used as the substrate to select the strains with high nervonic acid production from four oil-producing strains. The fermentation conditions of the selected strains were optimized by single factor experiment and response surface methodology. The composition and content of fatty acids in the lyophilized powder of the selected strains obtained by fermentation with or without Moringa oleifolia seed oil emulsion (volume ratio of Moringa oleifolia seed oil, water and Tween 80 2∶ 2∶ 1) were determined by GC-MS. The results showed that Saccharomyces rhodospora GDMCC 2226 was the best strain to produce nervonic acid. The optimal fermentation conditions of Saccharomyces rhodospora GDMCC 2.226 were as follows: Moringa oleifolia seed oil (in the form of emulsion) dosage 7%, bacterial fluid dosage 10%, culture temperature 28 ℃ and culture time 48 h. Under these conditions, the content of nervonic acid in the extract of Saccharomyces rhodospora GDMCC 2226 was 2.40 mg/mL. The contents of saturated fatty acids, monounsaturated fatty acids and polyunsaturated fatty acids (accounting for total fatty acids) in lyophilized powder of Saccharomyces rhodospora GDMCC 2.226 obtained by fermentation without Moringa oleifolia seed oil emulsion(control) were 38.91%, 41.92% and 19.18%, respectively, and the content of nervonic acid was 10.983 μg/g. The contents of saturated fatty acids, monounsaturated fatty acids and polyunsaturated fatty acids (accounting for total fatty acids) were 48.57%, 31.98% and 19.46%, respectively, and the content of nervonic acid was 13.518 μg/g in the lyophilized powder of Saccharomyces rhodospora GDMCC 2.226 obtained by fermentation with Moringa oleifolia seed oil emulsion, and its absolute content of nervonic acid was 23.1% higher than that of the control. In conclusion, adding Moringa oleifolia seed oil substrate can increase the absolute content of nervonic acid in the lyophilized powder of strain.